Legal Protection For Bank Customers Regarding The Disclosure Of Financial Information By Tax Authorities Based On Law Number 9 Of 2017 And Law Number 27 Of 2022 - Ewi Banjarnahor; Didik Suhariyanto; Puguh Aji Hari Setiawan (jurnal.unprimdn.ac.id, 2026)
This research examines the legal tension between the state’s interest in tax collection and the protection of bank customers’ privacy rights under two regimes: Law No. 9 of 2017 on Access to Financial Information for Tax Purposes and Law No. 27 of 2022 on Personal Data Protection, alongside bank secrecy provisions in Law No. 10 of 1998. The expanded authority of tax authorities to access financial data aims to enhance transparency and compliance but risks infringing privacy rights. Using a normative juridical method with statutory, conceptual, and case approaches, the study analyzes key legal sources, including the 1945 Constitution and Constitutional Court Decision No. 102/PUU-XV/2017. The analysis applies the principle of proportionality, as well as theories of legal protection (Philipus M. Hadjon) and legal certainty (Gustav Radbruch). Findings indicate that legal protection for bank customers remains largely formal and lacks substantive safeguards. Broad access by tax authorities is not matched by clear mechanisms of oversight, accountability, and legal responsibility. Normative overlap between tax disclosure rules and personal data protection obligations creates legal uncertainty for both financial institutions and customers. The study concludes that regulatory harmonization is necessary to resolve these conflicts. It recommends establishing an independent supervisory body and strengthening accountability frameworks to ensure a proportional balance between effective tax enforcement and the protection of citizens’ privacy rights. Penelitian ini menggunakan metode hukum normatif dengan pendekatan perundang-undangan, konseptual, dan kasus. Bahan hukum primer meliputi UUD NRI Tahun 1945, UU No. 9 Tahun 2017, UU No. 27 Tahun 2022, serta Putusan Mahkamah Konstitusi No. 102/PUU-XV/2017. Analisis dilakukan secara deskriptif-analitis dengan menelaah disharmoni norma dan penerapan asas proporsionalitas dalam pembatasan hak privasi. Pendekatan konseptual digunakan untuk mengkaji teori perlindungan hukum Philipus M. Hadjon dan teori kepastian hukum Gustav Radbruch sebagai pisau analisis terhadap pelaksanaan kebijakan keterbukaan informasi keuangan. Hasil penelitian menunjukkan bahwa perlindungan hukum terhadap nasabah bank dalam pelaksanaan keterbukaan informasi keuangan masih bersifat formal dan belum substansial. Akses data keuangan oleh otoritas pajak belum diimbangi dengan mekanisme pengawasan, akuntabilitas, dan tanggung jawab hukum yang jelas. Terdapat tumpang tindih antara kewenangan fiskus dalam UU No. 9 Tahun 2017 dan kewajiban perlindungan data pribadi dalam UU No. 27 Tahun 2022, yang menimbulkan ketidakpastian hukum bagi lembaga keuangan dan nasabah. Oleh karena itu, diperlukan harmonisasi regulasi dan pembentukan lembaga pengawas independen untuk menjamin keseimbangan antara efektivitas fiskal dan perlindungan hak privasi warga negara.